Acid‐Labile Acyclic Cucurbit[n]uril Molecular Containers for Controlled Release. Issue 41 (5th September 2017) - Mao, Dake; Liang, Yajun; Liu, Yamin; Zhou, Xianhao; Ma, Jiaqi; Jiang, Biao; Liu, Jia; Ma, Da
Abstract: Stimuli‐responsive molecular containers are of great importance for controlled drug delivery and other biomedical applications. A new type of acid labile acyclic cucurbit[ n ]uril (CB[ n ]) molecular containers is presented that can degrade and release the encapsulated cargo at accelerated rates under mildly acidic conditions (pH 5.5–6.5). These containers retain the excellent recognition properties of CB[ n ]‐type hosts. A cell culture study demonstrated that the cellular uptake of cargos could be fine‐tuned by complexation with different containers. The release and cell uptake of cargo dye was promoted by acidic pH. Abstract : Acyclic cucurbit[ n ]uril (CB[ n ]) molecular containers can degrade and release encapsulated cargo at accelerated rates under mildly acidic conditions (pH 5.5–6.5). These containers retain the excellent recognition properties of CB[ n ]‐type hosts. A cell culture study demonstrated that cargo uptake could be fine‐tuned by complexation with different containers. Release and cell uptake of cargo dye was promoted by acidic pH.